Arduino networking : connect your projects to the web using the Arduino Ethernet library - Schwartz, Marco (Community experience distilled., 2014)
This book is intended for those who want to build their own network-connected projects using the Arduino platform. You will be able to build exciting projects that connect to your local network and the Web. You will need to have some basic experience in electronics and web programming languages. You will also need to know the basics of the Arduino platform as the projects mainly deal with the networking aspects of the Arduino Ethernet shield.